2018
DOI: 10.1002/cam4.1596
|View full text |Cite
|
Sign up to set email alerts
|

ARNT/HIF‐1β links high‐risk 1q21 gain and microenvironmental hypoxia to drug resistance and poor prognosis in multiple myeloma

Abstract: Abstract1q21 gain is a common cytogenetic abnormality featuring high‐risk multiple myeloma (HRMM). However, the molecular mechanism underlying the adverse prognostic effect of 1q21 gain remains largely unclear. Here, we report that ARNT/HIF‐1β, a 1q21 gene, is highly expressed in HRMM and induced by microenvironmental hypoxia, which confers drug resistance and correlates with inferior outcome. Analysis of the gene expression profile database revealed that ARNT expression was upregulated in MM and increased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…Another possible cause of instability is the overexpression of the chromatin modifying enzymes, such as KDM4A. KDM4A is a histone demethylase, which binds the BCL9 locus and causes the rereplication and site-specific copy number gains of 1q12 and 1q21 43 , altered expression of microRNAs, and selective pressures, such as hypoxic stress 4446 . The induced gains of 1q12 and 1q21 reported in these studies are not stably inherited but transiently regenerated in subsequent S phases, just as in ICF syndrome and MM.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible cause of instability is the overexpression of the chromatin modifying enzymes, such as KDM4A. KDM4A is a histone demethylase, which binds the BCL9 locus and causes the rereplication and site-specific copy number gains of 1q12 and 1q21 43 , altered expression of microRNAs, and selective pressures, such as hypoxic stress 4446 . The induced gains of 1q12 and 1q21 reported in these studies are not stably inherited but transiently regenerated in subsequent S phases, just as in ICF syndrome and MM.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that genes located in the 1q21 amplicon, including CKS1B , PSMD4, IL6R, ADAR, MCL1 , and others, are associated with tumor proliferation and/or drug sensitivity because of upregulation of the expressed genes resulting from the increased gene dosage in MM cells with 1q21+ [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. It has been demonstrated by experimental cellular models, and/ or correlation analysis of gene expression levels and prognosis in a large patient cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Complete remission (CR) ratio of VTD was lower than those of VRd (38.5% vs. 59%), while the imaging CR ratio of VTD was similar to that of VRd using PET-CT (63.9% vs. 62%) [ 96 , 97 ]. Thus, VTD is considered to be effective for myeloma in hypoxia due to the release of EMD by THAL although hypoxia induces resistance for BOR [ 98 ].…”
Section: Myeloma Cells In Hypoxia and Vascular Nichementioning
confidence: 99%